Legalitas Pelaporan Kepada Anggota DPRD Dalam Menyampaikan Pendapat - Tomagola, Jihan; Supusepa, Reimon; Pattinasarany, Yohanes (PATTIMURA Law Study Review, 2025)
The statement made by the Chairman of Commission IV of the Maluku Regional People's Representative Council (DPRD), Samson Atapary, regarding the findings of the 2022 Maluku Provincial Scout Movement Regional Scout Movement (Kwarda) grant funds amounting to Rp. 2.5 billion fictitious amounts, and allegedly the PDI Perjuangan politician said that the management of the grant funds was managed by the Chairman of the Maluku Kwarda, Widya Pratiwi Murad and treasurer Ritha Hayat, resulted in the representative of the West Seram constituency being reported to the Maluku Police, Saturday (22/07/2023) this afternoon. The reporters who visited the Maluku Police office in Tantui came en masse. They consisted of elements of youth leaders, DPD KNPI Maluku, community leaders, traditional leaders and Upulatu from the Leihitu Peninsula, whose purpose was to report Samson Atapary for his statement which according to them had defamed Widya Pratiwi Murad Ismail. This research uses normative research methods conducted with a legislative approach, conceptual approach, and case approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The techniques for collecting legal materials and analyzing legal materials in the research include reading and reviewing various types of literature relevant to the research issues and directly related to the problems being studied. The DPRD in carrying out its duties and authorities as mentioned, the DPRD has the rights as regulated in Law Number 17 of 2014.Regarding the People's Consultative Assembly, the House of Representatives, the Regional Representative Council, and the Regional House of Representatives, have the following rights: (a). The right to interpellation (b) The right to inquiry (c) The right to express opinions.